Hypoxic hepatitis in cardiac intensive care unit: a study of cardiovascular risk factors, clinical course, and outcomes - Chávez-Tapia NC; Balderas-Garces BV; Meza-Meneses P; Herrera-Gomar M; García-López S; Gónzalez-Chon O; Uribe M (Dove Medical Press, 2014)
Norberto C Chávez-Tapia,1 Brenda V Balderas-Garces,1 Patricia Meza-Meneses,1 Magali Herrera-Gomar,2 Sandra García-López,2 Octavio Gónzalez-Chon,2 Misael Uribe1 1Obesity and Digestive Diseases Unit, 2Coronary Care Unit, Medica Sur Clinic and Foundation, Mexico City, Mexico Introduction: Hypoxic hepatitis (HH) is observed frequently in intensive care units. Information in the cardiac intensive care unit (CICU) is limited. The aim of this study was to analyze the clinical course and outcomes of HH in the specific setting of the CICU. Methods: We analyzed records of patients with HH admitted to the CICU (Group 1). Data were collected and compared with those of an intermediate group of patients with altered liver test results that did not meet the HH criteria who had a serum aminotransferase level of five to ≤20 times the upper-normal limit (Group 2), and with a control group who had an aminotransferase level less than five times the upper-normal limit (Group 3). Results: Patients with HH exhibited a worse hemodynamic profile and more of these patients were in shock: 17 (94.4%) in Group 1, 14 (77.8%) in Group 2, and seven (38.9%) in Group 3 (P=0.001). Cardiogenic shock was the most frequent event: 12 (66.7%) in Group 1, 13 (72.2%) in Group 2, and six (33.3%) in Group 3 (P=0.006). The mortality rate was 55.6%. Mechanical ventilation was an independent factor associated with death (odds ratio 12.25, 95% confidence interval 1.26–118.36). Conclusion: The mortality rate of patients with HH in CICU is high and is associated with ventilatory disturbances. Keywords: liver dysfunction, mechanical ventilation, hospital mortality